Analyzing Lamprey Population Growth and Sex Ratio Evolution Through Cellular Automata and Impact of Predation Efficiency and Sex Ratio on Lamprey Populations - He, Liwen; Cong, Zilin; Cai, Yanjing (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Lamprey plays an important role in the ecosystem, and studying its population dynamics and the evolution of sex ratio is essential to maintaining the balance of the ecosystem. Faced with the challenges of complex environmental interactions and changes in population parameters, this study simulates the impact of gender ratio shifts on lamprey populations, revealing that imbalanced sex ratios can reduce growth and alter community dynamics. Adult mortality and recruitment rates significantly affect these dynamics. Maintaining balanced sex ratios is crucial for lamprey conservation and management. Changes in the sex ratio of lampreys can affect reproductive rates, reduce the stability of ecosystems, and lead to changes in resource allocation. The final result is that the change of the sex ratio of lamprey will reduce the stability of the ecosystem, other races and food chains will be affected, and the balance of the ecosystem will also be affected. Based on these two models, this experiment finally concluded that changes in the sex ratio of lampreys may affect the reproduction rate, reduce the stability of the ecosystem, affect other species in the food chain and species living in the same area, and ultimately affect the stability of the ecosystem.